Clinical Study of Herpes Zoster In children CLINICAL STUDY OF HERPES ZOSTER IN CHILDREN (Journal of Misan Researches, 2020)
This disease is one of the acute viral diseases due to the reactivation of the virus that causes chicken pox (chickenpox). This study was done to determine the age and gender of the infected, as well as the location of the infection and the type of clinical signs of the infected. injury . (31) cases of infection were recorded during the one-year period of the study, the average age of the injured was 6.6 years, the number of males was 17 (54.8%) and the number of females (14) (46.2%). The injuries are as follows: the chest area (12) 38.7%) the lumbar region and the sacrum (14) (45.2%), the neck area (5) (16.1%), and for clinical signs the numbers were as follows: acute vesicular rash (22) (71%), covered or covered rash (8) (25.8%), post-infection neuritis (1) (3.2%)